2020
DOI: 10.3390/app10082664
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Melting Kinetics of Sugar-Reduced Silver Ear Mushroom Ice Cream under Various Additive Models

Abstract: This study focuses on assessing the effects of various food processing silver ear (Tremella fuciformis) powders in sugar-reduced ice cream through melting kinetic simulation, sensory properties and functional ingredients. T. fuciformis, a natural anti-melting stabilizer in ice cream, has the advantage of functional ingredients. Using 100, 200, and 300 mesh of particle sizes, and then selecting a suitable particle size, those are added to the additive ratios of 0.4, 0.9, and 1.4% T. fuciformis powder to replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The melting properties of the sorbets containing jujube did not differ significantly. Other authors [ 32 ] have also found that frozen dessert usually liquify for a period of 90 min.…”
Section: Resultsmentioning
confidence: 92%
“…The melting properties of the sorbets containing jujube did not differ significantly. Other authors [ 32 ] have also found that frozen dessert usually liquify for a period of 90 min.…”
Section: Resultsmentioning
confidence: 92%
“…In this research, the alteration of firmness and apparent viscosity happened because BPP and CP released volatile oil during the process into the ice cream mixture which contributed to the differentiation of the firmness and apparent viscosity 9 , 19 . Changes in firmness and apparent viscosity were also found when fermented pepper powder and silver ear mushroom powder were added to ice cream because the volatile compounds and solid content from additional particles or powders can influence the initial and gradual growth of ice crystals and interrupt product native thermodynamic instability 17 , 23 .…”
Section: Resultsmentioning
confidence: 99%
“…In all experiments, high-purity nitrogen was used as the purge gas, with a flow rate of 50 mL/min. The samples were heated at rates of 4, 6 or 8 • C/min, with a temperature range of 30-300 • C; the initial temperature was 30 to 70 • C, the sample was heated at a rate of 4, 6, or 8 • C/min, then held at 70 • C for 3 min, and next cooled to −60 • C for determining the low-temperature characteristics and thermal stability of the samples [35].…”
Section: Differential Scanning Calorimetry (Dsc) Thermal Analysismentioning
confidence: 99%